Effective Industrial Relations and Conflict Management: Essential Requirements for Enhancing Productivity in Nigeria: Array - Okolie, Ugo Chuks; Ojomo, Awulika Happiness (Journal of Danubian Studies and Research, 2020)
In Nigeria today, the new phase of capitalist globalization is seeking to transform established notions and hence practices of industrial relations and industrial disputes management as at no other time. Under the aegis of a neo-liberal ideology that is rooted in a new labour capital relation, workers are being indoctrinated to believe that ideology, paradoxically, is dead; that capitalism is the end of human history; that established relations of exploitation are immutable; that workers must find accommodation within these relations; that employers can now do much as they please. The argument of this paper is that this approach is counter- productive because in practice, it has the potential of leading to more and not less conflict between the employer and the employee. Fundamentally it has major consequences for productivity at the individual, organizational and societal level. It is important to note that labour and management hold the key to the nation’s socio-economic development. This implies that their disposition can make or mar the economy as the case in Nigeria today. It is against this backdrop that this paper underscores the indispensability of effective management of industrial relations and industrial system is a fundamental requirement for enhancing the performance of the national economy. This paper utilized the methods of qualitative and syntheses of scientific literature as it relies on secondary data collected from books and journal articles, and were content analyzed in relation to the scope of the paper.